Identification of the Biomotor Ability of Female Swimming Athlete Dragon Wirayudha Kediri in 2023 - Fahrurrozy, M. H Farhan; Rizky, Muhammad Yanuar; Junaidi, Slamet (CV. Nusantara Sporta, 2024)
Reaching the highest peaks in sport requires careful planning from a young age. Sports coaching at preschool age in Indonesia aims to foster national identity and develop talented young athletes for regional, national, and international success. Female swimmers from the Dragon Wirayudha Kediri club consistently participate in regional championships. This research assists coaches in identifying the biomotor abilities of these athletes in 2023. Using a quantitative method, the study population includes the biomotor abilities of the club's female swimmers. The instruments involve tests and measurements of 7 physical condition components. Data analysis utilizes T-Score, converting raw data from each test item into T-Scores, which are then aggregated to determine the average, standard deviation, maximum, and minimum scores. Results indicate that 8.33% of athletes are in the very good category, 25% good, 33% fair, 25% poor, and 8.33% very poor. Overall, the biomotor abilities of Dragon Wirayudha Kediri's female swimmers in 2023 are sufficient, providing a reference for trainers to prepare effective training programs.